Essential oil of Tanacetum khorassanicum (Krasch.) Parsa - T Majd-jabari; A Rustaiyan; H Vatanpour (Institue of Medicinal Plants, ACECR, 2003)
There are a number of studies on the biology and chemistry of the Tanacetum genus. The purpose of this investigation was to analyza the chemical composition of the aerial parts of T. khorassanicum, an Iranian native plant. Water- distilled essential oil of T. khorassanicum (Krasch.) Parsa (Composirae) was examined by GC and GC/MS. Thirteen constituents representing 90% of the oil, were characterized of which Myroxide (19.80%), Comphor (16.40%), Isopulegone (13.42%), 1,8- Cineol (11.41%), Borneol (8.31%) and Geraniol (7.9%) were the main compounds identified.